Challenges and Teaching Strategies of English Teachers in Industrial Revolution 4.0 Era - Rezky Uspayanti (Universitas Sulawesi Barat, 2021)
This study aims to investigate the challenges and teaching strategies of English teachers in District Merauke. This study is a mix-method namely the combination of qualitative and quantitative methods. 16 English teachers as the participants in the study from six high schools in Merauke district namely Senior High School 1 Merauke, Senior High School 2 Merauke, Senior High School 3 Merauke, Vocational High School 3 Merauke, Senior High School YPK Merauke, and MA Al-Munawwaroh. Data collection instruments used were questionnaires and interviews. Questionnaires used consisted of 40 statements and the interview consisted of 14 questions related to challenges and strategy of teaching English in the era of industrial revolution 4.0. As a result, challenges in the teaching and learning process are, especially for online learning. Mostly the students are constrained in technology facilities and motivation of students. While for the strategy in teaching English in industrial revolution era 4.0, by motivating students about the importance of English, providing variations in learning such as the use of video, audio, practice variety questions, using the online application (WhatsApp, google classroom, google translate, zoom, google meet, etc). Besides, by using discussions, question and answer directly, blended learning method, discovery learning, using image media, audio Lingual Method, TPR, GT, using voice note. Thus, by merging cognitive, affective, and psychomotor processes. Besides, for strategies in creating interesting and creative learning in the era of industrial revolution 4.0, by using jokes, games, giving advice, giving praise, and collaborating with native speakers in online learning.